New Proofs of Some q-Summation and q-Transformation Formulas - Xian-Fang Liu; Ya-Qing Bi; Qiu-Ming Luo (The Scientific World Journal)
We obtain an expectation formula and give the probabilistic proofs of some summation and transformation formulas of q-series based on our expectation formula. Although these formulas in themselves are not the probability results, the proofs given are based on probabilistic concepts.